2013
DOI: 10.1016/j.nucmedbio.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in vitro and in vivo characterization of two novel 68Ga-labelled 5-nitroimidazole derivatives as potential agents for imaging hypoxia

Abstract: Selective uptake and retention in tumour together with favourable tumour/muscle ratio make these compounds promising candidates for further evaluation as potential hypoxia imaging agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…HBED-CC has been successfully applied in the theranostics of prostate cancer when conjugated to the prostate-specific membrane antigen (PSMA) (Virgolini et al, 2017 ) but the combination with oxygen sensitive groups is yet to been investigated. Gallium-68 labeled nitroimidazole complexes were studied in mice models with induced (xenografted) tumors for CT26 (colon cancer) (Seelam et al, 2015 ), A549 (Wu et al, 2015 ) or 3LL (Fernández et al, 2013 ) (lung cancer cell lines). The comparison with [ 18 F]F-FMISO revealed successful hypoxia imaging and improved clearance properties.…”
Section: Preclinical and Clinical Imaging Of Hypoxiamentioning
confidence: 99%
“…HBED-CC has been successfully applied in the theranostics of prostate cancer when conjugated to the prostate-specific membrane antigen (PSMA) (Virgolini et al, 2017 ) but the combination with oxygen sensitive groups is yet to been investigated. Gallium-68 labeled nitroimidazole complexes were studied in mice models with induced (xenografted) tumors for CT26 (colon cancer) (Seelam et al, 2015 ), A549 (Wu et al, 2015 ) or 3LL (Fernández et al, 2013 ) (lung cancer cell lines). The comparison with [ 18 F]F-FMISO revealed successful hypoxia imaging and improved clearance properties.…”
Section: Preclinical and Clinical Imaging Of Hypoxiamentioning
confidence: 99%
“…49 The results obtained were comparable with reference images obtained with [ 18 F]FMISO and [ 18 F]FAZA, but the usage of methylated 5-nitroimidazole improved performance of 68 Ga-DOTA-nitroimidazoles in hypoxia imaging. 50…”
Section: General Oncology Imagingmentioning
confidence: 99%
“…Finally, cells were separated from supernatant and activity measured in order to compare the percentage taken up in normoxic and hypoxic conditions. This study has been previously validated by our group and used successfully in the evaluation of other [ 99m Tc]‐complexes . Results for [ 99m Tc(CO) 3 ( L )] showed that the ratio between hypoxic and normoxic uptake was 1.6 ± 0.4.…”
Section: Resultsmentioning
confidence: 81%
“…This study has been previously validated by our group and used successfully in the evaluation of other [ 99m Tc]-complexes. [17][18][19] Results for [ 99m Tc(CO) 3 (L)] showed that the ratio between hypoxic and normoxic uptake was 1.6 ± 0.4. This result is statistically significant (p ˂ 0.05) and confirms selectivity towards hypoxia conditions.…”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation